The Effectiveness of the Sandpaper Latters Teaching Method in the Development of Children's Literacy in Islamic Plus Mutiara Kindergarten - Azzahra, Fatimah (AWLADY : Jurnal Pendidikan Anak, 2025)
This study aims to analyze the effectiveness of the application of the sandpaper letters method in improving early childhood literacy skills in Islamic Plus Mutiara Kindergarten in Bantul. This method uses a multisensory approach that allows children to recognize letters through the activity of seeing, touching, and tracing the shape of letters made from textured materials such as sandpaper. The research approach used is qualitative descriptive, with the research subjects consisting of group B children aged 5–6 years, classroom teachers, and school principals. Data was collected through observations, interviews, and documentation of learning activities. The results of the study show that the use of the sandy letter method has a significant positive influence on children's early literacy skills. Before learning, only 6 out of 15 children (40%) were able to recognize the initial letters correctly. After four meetings using this method, the number increased to 13 children (86%). In writing skills, an increase was also seen from 4 children (27%) to 12 children (80%) who were able to imitate letter shapes correctly. In addition, the child's concentration level increased from 33% to 73%, and the child's confidence increased from 30% to 75%. This improvement suggests that the sandy letter method not only supports cognitive development, but also the affective and psychomotor aspects of the child. Overall, the sandpaper letters method  has proven to be effective in developing early childhood reading and writing skills in a fun and meaningful way, and can be an alternative learning medium that supports the implementation of the Independent Curriculum based on the Montessori approach.